Implementasi Evaluasi Program Pendidikan yang Holistik dan Berkelanjutan untuk Memastikan Kualitas Pendidikan yang Optimal - Ilhami, M. Arya Hilal Ridho; Luthfiah, Maya Rosydiana; Ilyas, Muhammad Efendi; Amalia, Kaniati (TSAQOFAH, 2024)
This study aims to identify weaknesses in the education program that has been carried out, formulate concrete improvement recommendations, and implement these corrective measures to improve the quality of education produced. The research method in the preparation of this article is to use data obtained by researchers through journal references, e-books, and other information media that support the title that the researcher raises or that is relevant to the problem raised by the researcher. The results show that conducting a thorough evaluation will help educational institutions to identify the strengths and weaknesses of existing educational programs, so that continuous improvement and improvement can be made. The results of this study also highlight that holistic evaluation of educational programs involves various important aspects such as curriculum, teaching methods, teaching staff, learning, facilities, and student support.